2022
DOI: 10.1097/gox.0000000000004263
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Curve of an Absorbable Subcuticular Stapling Device in Plastic and Reconstructive Surgery

Abstract: Bloom, MBBS (Hons), FRACS (Plas)* Background: Learning curves can reflect a surgical trainee's rate of progress and competence in acquiring new skills. The INSORB subdermal staple device has been well established to facilitate decreased closure time across various surgical procedures, with similar cosmesis, healing, and consistency as those of standard subdermal sutures. This study is unique, as it demonstrated an observable learning curve with this device when used by a junior surgeon. Methods: Sixty-six pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…25 Deep dermal stapler usage may also be less effective for thinner skin that may present with factors such as chronic corticosteroid use. 25,26 Some users have felt that absorbable staples may result in dermal scarring, particularly in skin with darker pigmentation; however, scars from incisions closed with absorbable staples have been shown to be similar to scars from incisions closed by sutures in several studies, and no notable differences in scars were visually observed in this study cohort. 11,17 This study is subject to several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Deep dermal stapler usage may also be less effective for thinner skin that may present with factors such as chronic corticosteroid use. 25,26 Some users have felt that absorbable staples may result in dermal scarring, particularly in skin with darker pigmentation; however, scars from incisions closed with absorbable staples have been shown to be similar to scars from incisions closed by sutures in several studies, and no notable differences in scars were visually observed in this study cohort. 11,17 This study is subject to several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the associated benefits in operation efficiency, the nuances of such usage must also be considered. For example, Singhal et al detected a notable learning curve in closure speed with application of absorbable subcuticular staples over 6 months when compared with traditional 3-0 Monocryl sutures, which suggests that surgeons who have never used the deep dermal stapler will need to invest some time to become proficient in its use 25 . Deep dermal stapler usage may also be less effective for thinner skin that may present with factors such as chronic corticosteroid use 25,26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation